The Effect of Discovery Learning Method Applications in Increasing Student Learning Motivation at MTs Islamic Boarding School of Salman Al-Farisi Karanganyar Solo - Muhammad Fathul Khoiruddin (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2020)
This study aims to discuss how the implementation of the Discovery Learning method in MTs Salman Al-Farisi Islamic Boarding School, Karanganyar Solo; and is there an effect of the Discovery Learning method on student learning motivation implemented at MTs Pondok Pesantren Ssalman Al-Farisi Karanganyar Solo. The form of this research is quantitative research that uses a population, because it is all grade VII students at MTs Pondok Pesantren Salman Al-Farisi Karanganyar Solo. In data collection, the authors used data collection techniques in the form of observation, interview (interview), documentation, and questionnaires. To find out the implementation of the Discovery Learning method and student learning motivation the writer used the percentage formula, while to determine whether the Discovery Learning method had an effect on student learning motivation the writer used the product moment formula (rxy). The results of this study indicate that there is no effect of the Discovery Learning method application on student learning motivation with a score of 0.077. If you look at the interpretation table, the value of "r" product moment is in the range 0.00 - 0.20, which means that between variable x and variable y there is a very weak or very low correlation (it is assumed that there is no correlation between the two).